2015
DOI: 10.1159/000369342
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Unc93b1</i></b>-Dependent Endosomal Toll-Like Receptor Signaling Regulates Inflammation and Mortality during Coxsackievirus B3 Infection

Abstract: Coxsackievirus strain B serotype 3 (CVB3)-inducedmyocarditis is an important human disease that causes permanent tissue damage and can lead to death from acute infection or long-term morbidity caused by chronic inflammation. The timing and magnitude of immune activation following CVB3 infection can mediate a positive host outcome or increase tissue pathology. To better elucidate the role of endosomal Toll-like receptor (TLR) signaling in acute CVB3 infection, we studied mice with a loss-of-function mutation, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…In various neurological diseases, the expression of SERPINA3N in the brain has been found to be significantly upregulated . Recent studies have also shown that SERPINA3N is clearly related to many inflammation‐related diseases, such as hypothalamic inflammation, retinal neuroinflammation, allergic airway inflammation, myocarditis, and atherosclerosis . Strikingly, the underlying mechanisms of SERPINA3N‐mediated inflammation have still not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In various neurological diseases, the expression of SERPINA3N in the brain has been found to be significantly upregulated . Recent studies have also shown that SERPINA3N is clearly related to many inflammation‐related diseases, such as hypothalamic inflammation, retinal neuroinflammation, allergic airway inflammation, myocarditis, and atherosclerosis . Strikingly, the underlying mechanisms of SERPINA3N‐mediated inflammation have still not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest that TLR3 senses the dsRNA intermediate produced during CVB replication, and that this sensing and subsequent activation of innate immune signaling is key to the control of CVB infection. Indeed, recent work has shown that Unc93b1 LETR/LETR mice, which have a loss of function mutation in the gene encoding Unc93b, exhibit increased mortality upon CVB-induced myocarditis due to higher viral titers and dysregulation of inflammation in these mice [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, analysis of microarray data [ 20 ] using DAVID [ 26 , 27 ] from cardiac tissue of wild-type mice versus Unc93b1 LETR/LETR mice found that there was a significant enrichment in the expression of genes involved in cell death pathways in CVB-infected wild-type animals (p = 0.0051), suggesting that Unc93b might play a role in cell death signaling during CVB infection. In addition, given that Unc93b has been directly linked to CVB-induced pathogenesis in vivo , we examined whether Unc93b was involved in cell death signaling during infection.…”
Section: Introductionmentioning
confidence: 99%
“…UNC93B is a transmembrane protein localized to the ER that is required for this trafficking (40,41). Mice with a nonfunctional UNC93B fail to respond to TLR3, TLR7, or TLR9 ligands, and mice and humans deficient in UNC93B are highly susceptible to viral infection (42)(43)(44).…”
mentioning
confidence: 99%